Implementation of an Anaesthesia Quality Improvement Programme to Reduce Fibreoptic Bronchoscope Repair Incidents. (21st March 2020) - Lu, Hsiao-Feng; Hung, Kuo-Chuan; Chiang, Min-Hsien; Yang, Johnson Chia-Shen; Luo, Sheng-Dean; Chin, Jo-Chi; Wang, Chih-Hsien; Sun, Cheuk-Kwan; Wu, Shao-Chun
Abstract : Background . This study was aimed at investigating the effectiveness of the implementation of a comprehensive quality improvement programme (QIP) for reducing the repair rate of the fibreoptic bronchoscope (FOB). Methods . A three-stage improvement strategy was implemented between January 2013 and December 2016. Stage one is the acquisition of information on violations of practice guidelines, repair rate, cost of repair, and incidence of unavailability of FOB during anaesthesia induction of the previous year through auditing. Stage two is the implementation of a quality improvement campaign (QIC) based on the results of stage one. Stage three is the programme perpetuation through monitoring compliance with policy on FOB use by regular internal audits. The effectiveness was retrospectively analyzed on a yearly basis. Results . The annual repair rate, repair cost, and incidence of FOB unavailability before the QIP implementation were 1%, 18, 757 USD, and 1.4%, respectively. After QIC, the repair rate in 2013 dropped by 81% (from 1% in 2012 to 0.19% in 2013, p < 0.05 ). The annual repair cost fell by 32% from 18, 758 USD (2012) to 12, 820 USD (2013). Besides, the incidence of FOB unavailability plummeted by 71% from 1.4% to 0.4% during the same period. The annual repair rates and incidence of FOB unavailability remained lower in subsequent three years than those before QIP implementation. Conclusion . Implementation of a quality improvement programme was effective for reducing the rate and cost of FOB repair as well as unavailability rate, highlighting its beneficial impact on cost-effectiveness and patient safety in a tertiary referral center setting.